Sonaten fur Klavier zu Zwei Handen I - BEETHOVEN (Edition Peters, 1927)
Di dalam buku ini terdapat 11 lagu: Sonate Op.2 No.1; Sonate Op.2 No.2; Sonate Op.2 no.3; Sonate Op.7; Sonate Op.10 No.1; Sonate Op.10 No.2; Sonate Op.10 No.3; Sonate Op.13; Sonate Op.14 Nt.1; Sonate Op.14 No.2; Sonate Op.22;